The Influence of Gender Equality on Indonesia's Economic Growth - Hasta Dwi Pradana; Ely Wahyuni (STIE Amkop Makassar, 2023)
This study explores the correlation between gender equality and economic growth in Indonesia. Using secondary data encompassing 34 provinces over the period 2021-2022, the research employs regression analysis with a panel data approach and utilizes the Fixed Effect Model (FEM) as its quantitative framework. The regression results indicate an overall significant positive impact of variables involved in gender equality. The Gender Development Index (GDI) variable shows an essential impact supporting economic growth with a positive trend. However, the results indicate that the Gender Empowerment Index (GEI) has a negative influence on economic growth. Furthermore, the Labor Force Participation Rate (LFPR) does not support Indonesia's economic expansion. This analysis highlights the necessity of increased full participation of women across various sectors to foster economic growth. Recognizing that gender inequality will persist unless the role of women is strengthened, the study emphasizes the need to empower women to achieve gender equality. This study, by establishing an attained focus on fairness, reinforces the notion that the Indonesian economy will thrive through the active involvement and contributions of all segments of society.